مشروعية استخدام المعدات الأمنيّة أثناء المظاهرات وفقاً لأحكام الشريعة الإسلامية - Ibrahim Meftah Alfellag; Ruzman Bin Md Noor (Universitas Islam Negeri Jakarta, 2016)
This paper deals with the review of the equipment used by security officers during demonstrations by explaining their concept and the two types of equipment namely lethal and non-lethal, and detailing their types which have been used currently. This paper also evaluates the legitimacy of their usages in accordance with the provisions of Islamic law and related Islamic Law views. This study has concluded that it is illegal to use these type of equipment except in specific cases and under certain conditions to avoid certain imminent danger.DOI: 10.15408/ajis.v16i1.2904